2003
DOI: 10.1108/14684520310471680
|View full text |Cite
|
Sign up to set email alerts
|

Modern Hebrew literature on the Web: a content analysis

Abstract: In this study, a set of freely accessible Web sites were examined, as a first step in understanding the ways the Web is utilised for disseminating, publishing, discussing, studying and selling modern Hebrew literature. The sites were classified according to different facets using the method of content analysis. The results show that amateurs have great interest in publishing their works on the Web, either on their own private sites or on sites that encourage the users to upload their literary works and to inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The first strand of existing research deals with poetry distribution (Bar-Ilan and Groisman, 2003; Bolter, 2001; Glazier 2002). It shows that new possibilities for poetry distribution arise due to the general curiosity about the web as well as the dramatic weakening of the former literary spaces described by Bolter, including poetry readings, university literature departments, and book and newspaper distribution (Bolter, 2001).…”
Section: Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first strand of existing research deals with poetry distribution (Bar-Ilan and Groisman, 2003; Bolter, 2001; Glazier 2002). It shows that new possibilities for poetry distribution arise due to the general curiosity about the web as well as the dramatic weakening of the former literary spaces described by Bolter, including poetry readings, university literature departments, and book and newspaper distribution (Bolter, 2001).…”
Section: Distributionmentioning
confidence: 99%
“…The creative community on the web is an expression of the poets’ desire for a lively discussion with readers about their work. A study from 2003 that sampled a subset of websites found that poetry constitutes 70% of the literary texts on the web (Bar-Ilan and Groisman, 2003). This contributes to the fact that the majority of online literary discourse concerns poetry.…”
Section: Distributionmentioning
confidence: 99%
See 1 more Smart Citation